1996
DOI: 10.1111/j.1751-0813.1996.tb14816.x
|View full text |Cite
|
Sign up to set email alerts
|

Residues from long‐acting antimicrobial preparations in injection sites in cattle

Abstract: A review of the maximum injection volume, site of injection and the withholding period is needed for long-acting OTC formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Therefore, the finding of no significant difference between GnRH and saline may be confounded with this smaller volume. Volume of injection has been associated with size of the injection site lesion (Mawhinney et al, 1996), although this was for the long-acting antibiotic oxytetracycline. We elected to use the dosages of drugs used clinically in this first investigation into the assessment of muscle damage because we had no hypothesis as to the impact of volume of injection.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the finding of no significant difference between GnRH and saline may be confounded with this smaller volume. Volume of injection has been associated with size of the injection site lesion (Mawhinney et al, 1996), although this was for the long-acting antibiotic oxytetracycline. We elected to use the dosages of drugs used clinically in this first investigation into the assessment of muscle damage because we had no hypothesis as to the impact of volume of injection.…”
Section: Discussionmentioning
confidence: 99%
“…administration, injection volume influences both the quantity of tissue discarded (George et al. , 1997) and the concentration of residues at injection sites (Mawhinney et al. , 1996).…”
Section: Issues That Set Injection Site Residues Apartmentioning
confidence: 99%
“…, 1996). Studies in cattle demonstrated that the administration of 10 mL or less of long‐acting oxytetracycline per injection site resulted in minimal tissue damage and an absence of cysts with residues at the injection site of 0.1 mg/kg or less at 45 days postinjection (Mawhinney et al. , 1996).…”
Section: Issues That Set Injection Site Residues Apartmentioning
confidence: 99%
See 2 more Smart Citations